Job Satisfaction as A Predictor of Organizational Citizenship Behavior In Employees of PT. X Cirebon - Fiera Maga, Solagratia Angelita; Prapunoto, Susana (Green Publisher Indonesia, 2022)
This study aims to determine job satisfaction as a predictor of organizational citizenship behavior (OCB) in employees of PT. X in Cirebon. The population in this study amounted to 31 people who were also the sample in this study also taken using total sampling technique. The analytical method used is simple linear regression analysis. The results showed that job satisfaction has a positive and significant effect on organizational citizenship behavior (OCB) on employees of PT. X in Cirebon. The value of the determinant coefficient obtained is 13%, which means that job satisfaction contributes 13% to the OCB of employees of PT. X in Cirebon. The magnitude of the influence is indeed relatively small, namely 13% but this finding can still confirm that in general the employees of PT. X in Cirebon, OCB can be built with or in conjunction with job satisfaction